Food nation : fast food and its impact on social relations between Singaporeans. - Lim, Cheng Zhi. (2011)
Food consumption habits and patterns have always been a distinctive quality that highlights the identity of Singaporeans. Globalisation has contributed to a wave of food products sweeping into the nation in recent decades. In examining and comparing food consumption patterns between Singaporeans, this paper aims to find out specifically how fast-food has altered the construction of individual identity when it comes to food consumption. Views mainly from the younger generation between the ages of 20 and 25 are examined to understand how fast-food has impacted their lives since they grew up consuming fast-food. The paper touches on the localisation of fast-food both by consumers as well as the food corporations, how commensality is compromised for individualisation within fast-food context, and the power of consumption in consumers making food decisions.